Inovasi Kualitas Pelayanan Publik Pemerintah Daerah Di Indonesia - Fhariz El Habyb (CV. Ulil Albab Corp, 2025)
Innovation in the quality of local government public services in Indonesia is key to improving the effectiveness and efficiency of services to the public. This article examines the different types of innovations that have been implemented, including the utilisation of information technology, simplification of procedures, and the development of new service methods. Through a qualitative approach and literature review, this research finds that despite progress in innovation implementation, challenges such as budget constraints, resistance to change, and unsupportive regulations remain. Factors that influence innovation success include visionary leadership, supportive organisational culture, and human resource capacity. To overcome these challenges, this article recommends improving training for officials, strengthening collaboration between government agencies, and updating regulations. With these steps, it is hoped that public service innovation can continue to grow and have a positive impact on society. Overall, innovation in public services is an integral part of efforts to build responsive and accountable governance at the local level.